MYSTICAL RADIANCE OF MANUSCRIPT: A PARATEXTUAL STUDY OF ISLAMIC ASTRONOMY MANUSCRIPT - Kila, Syahrir; Hamsiati, Hamsiati; Hamid, Wardiah; Arsyad, Abd. Rahman; Idham, Idham; Nur, Muhammad; Nomay, Usman; Wan Sulaiman, Wan Shahrazad (Al-Qalam, 2024)
Society treating manuscripts as objects with mystical power is often viewed as a myth that has no scientific basis. There are differences of perspectives about mystical belief and reality that evoke supernatural phenomenon related to manuscripts. This research analyzes the paratextual aspects of the Islamic Astronomy Manuscript owned by Husen Hatuwe in Keitetu Village, Leihitu District, Central Maluku Regency. The manuscript is used as a guidance to determine the right time for various daily activities and considered to have mystical power by the local community. This research is a philological study which used data collection technique through observation, interviews, and literature studies. The paratextual approach in this research reveals the external narrative aspects of the manuscript, including how the local culture influences and get influenced by the existence of the manuscript. Apart from serving as a guidance to determine the right time for religious rituals, this manuscript is also Mystical Radiance of Manuscript … – Syahrir Kila, et.al | 253 believed to have spiritual power that maintains the social balance in the community. In addition, this research contributes to the attempt to preserve the ancient manuscripts in Maluku, which most of them are damaged due to inadequate storage as well as analyze the role of this manuscript in the social, spiritual, and cultural context of the local community.